PENYULUHAN DAN PEMBUATAN PAPER SOAP (SABUN KERTAS) BAGI MASYARAKAT DI KELURAHAN PEMATANG GUBERNUR KOTA BENGKULU UNTUK MENINGKATKAN KESADARAN MENCUCI TANGAN SEBAGAI LANGKAH AWAL PENCEGAHAN WABAH COVID-19 - Risky Hadi Wibowo; Sipriyadi Sipriyadi; Reza Pertiwi; Thoriqul Hidayah; Della Indah Medani; Gustina Dwi Wulandari; Nadya Rosianti (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Hand is the main transmission pathogen entry into the body which is the part of the body that is most often in direct contact with other limbs and surrounding objects. The importance of maintaining hand hygiene by always washing hands with soap is the first step in preventing transmission of COVID-19. However, during a pandemic like this, it will be difficult to find soap available everywhere, and tends to be hard to carry all the time. Therefore, this service aims to invite the people of Pematang Gubernur, Bengkulu City, to use paper soap because it is easier to use its use and flexible to carry anywhere besides being an effort to prevent the COVID-19 outbreak, it can also add to new information and skills for residents in making attractive soaps. The feedback response given by the community service implementation team to the community service participants resulted in a positive response to this activity, who initially did not know about making and use of paper soap and became aware of this.